The Role of Torovirus in Nosocomial Viral Gastroenteritis at a Large Tertiary Pediatric Centre - JB Gubbay; A Al-Rezqi; M Hawkes; L Williams; SE Richardson; A Matlow (Canadian Journal of Infectious Diseases and Medical Microbiology)
OBJECTIVE: To describe the viral etiology and epidemiology of nosocomial viral gastroenteritis (NVG) at a tertiary care pediatric hospital and identify any changes over the past two decades.